Industrial green technology innovation efficiency of China - Yao, Fengge; Qin, Zenan; Wang, Xiaomei (Frontiers in Environmental Science, 2022)
The industrial green technology innovation of a region is of great significance for promoting the high-quality development of the regional economy and promoting the construction of ecological civilization. Based on the panel data of 30 provinces (except Tibet) in China from 2010 to 2020, this paper uses the DEA model adding unexpected output to measure China’s industrial green technology innovation efficiency (IGTIE) under the common frontier and regional frontier. The results show that: (1) The IGTIE generally shows an upward trend, which is mainly due to technical progress and efficiency improvement. Under the common frontier, IGTIE has an average annual growth of 6.54%, and under the regional frontier, IGTIE has an average annual growth of 6.77%. (2) Whether under the common frontier or the regional frontier, the central region has obvious advantages in IGTIE compared with the western region and the eastern region. (3) Under the two frontiers, the western region is dominated by efficiency change. Finally, according to the empirical analysis results, specific policy recommendations are put forward for the improvement of China’s future industrial green technology innovation efficiency.